Analiza volilnega vedenja in izbir na prvih predčasnih volitvah v državni zbor 2011 - Kustec Lipicer, Simona (Teorija in praksa, 2013)
The main aim of this article is to describe and explain the relevant socio-psychological and political science characteristics of the pre- and post-electoral behaviour and electoral choices offered by political parties at the first early elections to the National Assembly held in December 2011. The analysed elections are an important milestone in the evolution of the Slovenian democratic parliamentary and party system and behaviour at the national level. The article examines the instability of the electoral capital of the electorate, as well as the decrease in parties' electoral capital with respect to modes of the future democratic governance system and related problem-solving.
Keywords: election; javno mnenje; nacionalni parlament; political party; politične stranke; Slovenia; Slovenija; volilci; volilni programi; volitve